THEORETICAL ANALYSIS OF QUASI-STATIC COMPRESSION OF HEXAGONAL RING - SAID, MD RADZAI (2011)
This paper presents a study on the load-compression and energy absorption characteristics of a laterally crushed across faces of hexagonal ring with constraints on expansion perpendicular to the loading axis. The theoretical analysis in compression across faces is developed using Equivalent Structure Technique. Experimental observations are compared with theoretical analyses and good agreements are seen.